Análise da gestão de resíduos sólidos urbanos em capitais do nordeste brasileiro: o caso de Aracaju-SE e João Pessoa-PB - Silva, Aline Carolina da (2014)
The Brazilian Federal Law number 12,305, August 2nd, 2010, which instituted the Brazilian National Solid Waste Policy (Política Nacional dos Resíduos Sólidos - PNRS), establishes deadlines for some actions, such as the removal of sanitary landfills and the environmentally appropriate waste disposal, by 2014. However, this Law, a historic mark in the environmental management of the country, is subject to failure in its implementation if there is not a commitment between all the political entities of the Brazilian federation. In this context, this study is aimed at analyzing the solid waste management in the cities of Aracaju (SE) and João Pessoa (PB), both located in the northeastern part of Brazil, focusing on the methods of final disposal, the collection programs, and the problems faced in the implementation of the Brazilian National Policy on Solid Waste. To achieve the main objective of the study, it was necessary to prepare an investigation concerning the administration and management of urban solid waste in João Pessoa and in Aracaju, in order to identify the technical, economic, and socio-environmental issues that encompass the subject. We gathered information about the methods of final disposal, the separate collection systems in the cities, the plans, the actions, the laws of each city, the practices performed as well as their infrastructures. These data allowed a comparison between the cities studied. The Data Collection Method used was the Primary Data and the Secondary Data. The collection instrument was the field research (extensive direct observation), and surveys. The methods of data analysis were quantitative and qualitative, represented by simple statistics in graphics, tables, charts and flowcharts. The results showed that the cities have similarities regarding the prospects of developing proposals to implement the policy, but both face difficulties related to technical training, financial resources, environmental awareness and meeting the deadlines established by the specific law. Also, we verified that, in general, the political issues in Brazil have influence in the decision-making, therefore affect the planning of the waste management systems, inhibiting successful experiences. It was also discovered that the cities lack a system for collecting consistent, comprehensive and standardized data on quantities, compositions of solid waste and quality indicators that enable the scope and efficiency of these data systems. This shows that there is a need to restructure all executive areas directly or indirectly responsible for this issue in Brazil. Only then, will it achieve the desired objectives in the legislation, and enable an effective supervision in order to provide continuity in the actions to be implemented.